2017
DOI: 10.2340/16501977-2170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bihemispheric anodal transcranial direct current stimulation for dysphagia in chronic stroke patients: A randomized clinical trial

Abstract: The bihemispheric anodal tDCS with conventional dysphagia therapy had additional helpful effects on the improvement in swallowing function in chronic stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 34 publications
2
55
1
1
Order By: Relevance
“…Transcranial direct current stimulation (tDCS) involves a low-intensity, electrical current (1–2 mA) applied between a cathode and anode placed on the scalp [ 76 , 79 ]. Anodal tDCS depolarizes the resting membrane potential and thereby increases neuronal excitability, whereas cathodal tDCS hyperpolarizes the resting membrane potential, decreasing neuronal excitability [ 79 ]. Anodal tDCS has been explored as a method to enhance swallowing recovery in dysphagic stroke patients.…”
Section: How Can We Improve Treatment Of Post-stroke Dysphagia?mentioning
confidence: 99%
See 2 more Smart Citations
“…Transcranial direct current stimulation (tDCS) involves a low-intensity, electrical current (1–2 mA) applied between a cathode and anode placed on the scalp [ 76 , 79 ]. Anodal tDCS depolarizes the resting membrane potential and thereby increases neuronal excitability, whereas cathodal tDCS hyperpolarizes the resting membrane potential, decreasing neuronal excitability [ 79 ]. Anodal tDCS has been explored as a method to enhance swallowing recovery in dysphagic stroke patients.…”
Section: How Can We Improve Treatment Of Post-stroke Dysphagia?mentioning
confidence: 99%
“…Anodal tDCS can be unilateral or bilateral. Unilateral anodal tDCS involves placing the anode over the affected pharyngeal motor cortex and the cathode over the contralateral supraorbital region, whereas bilateral tDCS places an anode over the pharyngeal motor cortex of both hemispheres and a cathode over each corresponding contralesional supraorbital region [ 79 ]. Dual stimulation utilizes both anodal and cathodal tDCS, implementing anodal tDCS over the damaged hemisphere and cathodal tDCS over the contralesional one [ 80 ].…”
Section: How Can We Improve Treatment Of Post-stroke Dysphagia?mentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that tDCS induced better improvements in functional dysphagia scale (FDS) at 3 months after tDCS [ 31 ] or in DOSS lasting for 1 month [ 32 ]. Effect of bihemispheric anodal tDCS (1 mA for 20 min, a total of ten tDCS sessions within 2 weeks) was tested by Ahn et al [ 33 ] in 26 post-stroke dysphagic patients and reported significant improvement in the patients who received tDCS but not in the sham group. These findings suggest that stimulating either hemisphere by anodal tDCS improve dysphagia and utility of this technique as an effective intervention for dysphagia rehabilitation.…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 99%
“…[ 4 – 8 ] Particularly, the patients with acute, subacute or chronic dysphagia induced by stroke can achieve substantial improvement of the swallowing function after receiving tDCS. [ 9 13 ] However, the sites where the electrodes of tDCS place very in the existing studies. The knowledge regarding whether there is difference between the effect of tDCS over the unaffected, affected or both hemispheres is limited.…”
Section: Introductionmentioning
confidence: 99%